Histomorphological investigations of some endocrine glands in peacock "Pavo cristatus" - Alshammary, Hanaa Kareem Ali (Diyala Journal for Veterinary Sciences, 2023)
Aims: to determine the location, shape and boundaries, in addition to the histological structures of some endocrine organs in the Peacock such as: Thyroid, Parathyroid and adrenal gland by absolute eyes and light microscope and leads to establish a definite description of these glands. Methods: ten adult healthy Peacock birds were taken and divided into two groups: anatomical and histological Results : Anatomically Peacock had a pair of symmetrical thyroid glands of spherical shape, dark red or reddish–brown color, lie at the end of neck parallel to trachea, in between jugular vein and common carotid artery. Peacock also had a pair of parathyroid glands, symmetrically location, each had cranial and caudal part, which were seen slightly separated from each other on the right side, while they were adhered to each other forming a single gland on the left side, while the adrenal glands appeared paired small structures positioned inside the celome on two sides of the median line beside the cranial poles of kidneys with a color ranged from yellowish to reddish-yellow. Histologically, thyroid parenchyma consisted of spherical follicles, and according to epithelial type, shape and colloid's nature inside them, follicles categorized into very active, in-active and active follicles. Parathyroid parenchyma comprised irregular anastomosing and branching cords composed of one type of cells the faintly stained chief cells. Adrenal parenchyma showed cortex intermingled with medulla and divided into two zones, peripheral and central. , , , , , .